2016
DOI: 10.1016/j.jpeds.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Correlates with Severity of Illness and Poorly Reflects Adrenal Function in Pediatric Acute Respiratory Distress Syndrome

Abstract: Objective To test the association between random cortisol and severity of illness in a “real-world” application of current guidelines. Study design We performed a secondary analysis of a prospective observational cohort of acute respiratory distress syndrome (ARDS). Children with ARDS and vasopressor-dependent shock were identified and random cortisol levels prior to potential hydrocortisone initiation recorded. The cohort was dichotomized to cortisol < 18 μg/dL and ≥ 18 μg/dL, and hydrocortisone use and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
(60 reference statements)
2
10
0
Order By: Relevance
“…While low rSTC levels in children with severe meningococcemia may directly reflect acute adrenal insufficiency (Waterhouse-Friderichsen syndrome) (2224), it is unclear whether rSTC levels directly correlate with adrenal function in the case of other critical illness settings such as non-meningococcal sepsis or trauma (25). The findings of our study are similar to other studies of critically ill children with severe sepsis (either alone, or in combination with other disease entities) that have observed strong positive correlation between rSTC levels and mortality, with higher levels in non-survivors (2628). Elevated rSTC levels in these circumstances likely arise due to ACTH independent mediators of release as well as from decreases in metabolism and clearance of cortisol as an adaptive mechanism in times of acute stress (29,30).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While low rSTC levels in children with severe meningococcemia may directly reflect acute adrenal insufficiency (Waterhouse-Friderichsen syndrome) (2224), it is unclear whether rSTC levels directly correlate with adrenal function in the case of other critical illness settings such as non-meningococcal sepsis or trauma (25). The findings of our study are similar to other studies of critically ill children with severe sepsis (either alone, or in combination with other disease entities) that have observed strong positive correlation between rSTC levels and mortality, with higher levels in non-survivors (2628). Elevated rSTC levels in these circumstances likely arise due to ACTH independent mediators of release as well as from decreases in metabolism and clearance of cortisol as an adaptive mechanism in times of acute stress (29,30).…”
Section: Discussionsupporting
confidence: 91%
“…As in other studies of critically ill children (13,14,28,34,35), SDH therapy conferred no definite benefits and, on the contrary, appeared to be associated with harm in this study cohort. Corticosteroids have numerous side effects including hyperglycemia, myopathy and delayed wound healing that predispose to morbidity and prolonged PICU dependency (36).…”
Section: Discussionsupporting
confidence: 52%
“…However, basal cortisol values were also correlated to disease severity, i.e., the higher PRISM III score was positively related to higher basal cortisol values; thus, absolute adrenal insufficiency (low basal cortisol) was not helpful in predicting higher disease severity. Yehya et al [18] also reported that pediatric patients with acute respiratory distress syndrome with vasopressor-dependent shock whose basal (random) cortisol values were <18 µg/dL were less sick (lower PRISM III scores, lower organ failures, and lower vasopressor scores) than those patients with random cortisol values of 18 µg/dL or above.…”
Section: Discussionmentioning
confidence: 99%
“…At least one pediatric [320] and several adult [321] interventional trials examining adjunctive corticosteroids for septic shock have concluded that this drug class hastens resolution of shock. Of the four adult, high-quality contemporary RCTs, two reported a mortality reduction and two did not [322][323][324][325][326]. A recent meta-analysis of 42 RCTs including 9969 adults and 225 children with sepsis found that corticosteroids possibly result in a small reduction in short-term mortality (RR, 0.93; 95% CI, 0.84-1.03), long-term mortality (0.94; 95% CI, 0.89-1.00), faster resolution of shock, and shorter LOS, while also possibly increasing the risk of neuromuscular weakness (RR, 1.21; 95% CI, 1.01-1.52) [327].…”
Section: Corticosteroidsmentioning
confidence: 99%